The Impact of Surgical Strategy and Rifampin on Treatment Outcome in Cutibacterium Periprosthetic Joint Infections. (10th December 2020) - Kusejko, Katharina; Auñón, Álvaro; Jost, Bernhard; Natividad, Benito; Strahm, Carol; Thurnheer, Christine; Pablo-Marcos, Daniel; Slama, Dorsaf; Scanferla, Giulia; Uckay, Ilker; Waldmann, Isabelle; Esteban, Jaime; et al.
Abstract: Background: Cutibacterium species are common pathogens in periprosthetic joint infections (PJI). These infections are often treated with β-lactams or clindamycin as monotherapy, or in combination with rifampin. Clinical evidence supporting the value of adding rifampin for treatment of Cutibacterium PJI is lacking. Methods: In this multicenter retrospective study, we evaluated patients with Cutibacterium PJI and a minimal follow-up of 12 months. The primary endpoint was clinical success, defined by the absence of infection relapse or new infection. We used Fisher's exact tests and Cox proportional hazards models to analyze the effect of rifampin and other factors on clinical success after PJI. Results: We included 187 patients (72.2% male, median age 67 years) with a median follow-up of 36 months. The surgical intervention was a 2-stage exchange in 95 (50.8%), 1-stage exchange in 51 (27.3%), debridement and implant retention (DAIR) in 34 (18.2%), and explantation without reimplantation in 7 (3.7%) patients. Rifampin was included in the antibiotic regimen in 81 (43.3%) cases. Infection relapse occurred in 28 (15.0%), and new infection in 13 (7.0%) cases. In the time-to-event analysis, DAIR (adjusted hazard ratio [HR] = 2.15, P = .03) and antibiotic treatment over 6 weeks (adjusted HR = 0.29, P = .0002) significantly influenced treatment failure. We observed a tentative evidence for a beneficial effect of adding rifampin to the antibiotic treatment—though not statistically significant for treatment failure (adjusted HR = 0.5, P = .07) and not for relapses (adjusted HR = 0.5, P = .10). Conclusions: We conclude that a rifampin combination is not markedly superior in Cutibacterium PJI, but a dedicated prospective multicenter study is needed. Abstract : In this retrospective study, we observed no significant benefit of using rifampin to avoid relapses or new infections but a benefit when the prosthesis was removed or exchanged and an antibiotic treatment was given for at least 6 weeks.